2008
DOI: 10.1038/sj.jcbfm.9600603
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Melatonin Increases in Cerebrospinal Fluid of Patients after Severe Traumatic Brain Injury and Correlates with Oxidative Stress and Metabolic Disarray

Abstract: Oxidative stress plays a significant role in secondary damage after severe traumatic brain injury (TBI); and melatonin exhibits both direct and indirect antioxidant effects. Melatonin deficiency is deleterious in TBI animal models, and its administration confers neuroprotection, reducing cerebral oedema, and improving neurobehavioural outcome. This study aimed to measure the endogenous cerebrospinal fluid (CSF) and serum melatonin levels post-TBI in humans and to identify relationships with markers of oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 43 publications
3
69
2
Order By: Relevance
“…This is the case despite the finding that the lipid peroxidation markers F2-isoprostane and malondialdehyde are increased in brain tissue, serum, and CSF after experimental and clinical TBI. [142][143][144] More importantly, this increase in lipid peroxidation is associated with worse clinical outcomes in patients with severe TBI. 145,146 Also unique is the fact that phospholipids in different regions of the brain differ in their fatty acid compositions and side chains, 132-134 but association among types of phospholipids, regions of brain injury, and rates of coagulopathy has not been examined.…”
Section: Phosphatidylserine and Brain Phospholipidsmentioning
confidence: 99%
“…This is the case despite the finding that the lipid peroxidation markers F2-isoprostane and malondialdehyde are increased in brain tissue, serum, and CSF after experimental and clinical TBI. [142][143][144] More importantly, this increase in lipid peroxidation is associated with worse clinical outcomes in patients with severe TBI. 145,146 Also unique is the fact that phospholipids in different regions of the brain differ in their fatty acid compositions and side chains, 132-134 but association among types of phospholipids, regions of brain injury, and rates of coagulopathy has not been examined.…”
Section: Phosphatidylserine and Brain Phospholipidsmentioning
confidence: 99%
“…81 Multiple studies have shown that brain injuries increase the levels of F2-isoprostane both in the CSF and the serum of TBI patients. [82][83][84] For example, Varma et al 85 demonstrated that in children who had severe TBI, the level of F2-isoprostane was elevated by 6-fold compared with that observed in uninjured controls. This marker was found to correlate well with the appearance of NSE, further supporting its use as an indicator of brain damage.…”
Section: F2-isoprostanementioning
confidence: 99%
“…To our knowledge, no study has examined whether IsoFs are altered in the CSF of patients after aSAH. Increased CSF F 2 -IsoPs have been reported in TBI patients (2,(7)(8)(9). To date, no study has examined IsoFs and F 4 -NeuroPs in patients with TBI.…”
Section: Innovationmentioning
confidence: 99%